1994
DOI: 10.1111/j.1398-9995.1994.tb02650.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the macrophage in asthma

Abstract: Aeeumulating evidence implicates eells ofthe mononuclear phagocyte lineage in the pathogenesis of bronchial asthma. The evidence for involvement of peripheral blood monoeytes (PBM) and alveolar macrophages (AM) in the pathogenesis of asthma stems from functional studies on peripheral blood monocytes and analysis of the fluid and cellular phases of bronchoalveolar lavage (BAE) samples, and, more recently, from histologic material obtained from endobronchial biopsy in vivo. -• Peripheral blood monocytesIn 1975, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 76 publications
1
18
0
1
Order By: Relevance
“…Alveolar macrophages are the most abundant cells, not only in the alveoli and distal air spaces but also in the conducting airways [18]. Activated alveolar macrophages may participate in the inflammatory events associated with allergic disease of the lower airways, including release of cytokines, chemokines, arachidonic acid metabolites, products of activated O 2 , and by direct interaction with T lymphocytes [19,20,21,22,23]. These studies suggested that MCP-1 and macrophages play important roles in the pathogenesis of bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophages are the most abundant cells, not only in the alveoli and distal air spaces but also in the conducting airways [18]. Activated alveolar macrophages may participate in the inflammatory events associated with allergic disease of the lower airways, including release of cytokines, chemokines, arachidonic acid metabolites, products of activated O 2 , and by direct interaction with T lymphocytes [19,20,21,22,23]. These studies suggested that MCP-1 and macrophages play important roles in the pathogenesis of bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alveolar macrophages (AMs) are the most abundant cells in not only the alveoli and distal air space but also conducting airways [16]. These AMs are activated in asthma [17], and may participate in inflammatory events such as the release of cytokines, chemokines, arachidonic acid metabolites, and products of activated O 2 -, which are associated with allergic disease of the lower airways, by direct interaction with T lymphocytes [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Activated macrophages secrete a wide variety of products and cause tissue repair and remodeling. Macrophages are significantly correlated with severity of asthma [18].…”
Section: E Macrophagesmentioning
confidence: 99%